Pengaruh Profesionalisme Kerja, Komitmen Organisasi Dan Keterikatan Kerja Terhadap Kinerja Karyawan (Studi Pada Guru SMK Muhammadiyah 1 Cipondoh): The Influence of Professionalism, Organizational Commitment, and Job Engagement on Employee Performance (A Study of Teachers at SMK Muhammadiyah 1 Cipondoh) - Puan Hapsari Murti; Yuni Kasmawati (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the influence of work professionalism, organizational commitment, and work engagement on employee performance of teachers at SMK Muhammadiyah 1 Cipondoh. This research uses a quantitative approach with a survey method. The population consisted of 39 teachers and all members of the population were used as samples using the saturated sampling technique. Data collection was carried out through questionnaires using a Likert scale, interviews, and observations. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS software. The results show that work professionalism has a positive and significant effect on employee performance with a p-value of 0.008 < 0.05. Work engagement also has a positive and significant effect on employee performance with a p-value of 0.000 < 0.05 and becomes the most dominant variable influencing employee performance. Meanwhile, organizational commitment has a positive but not significant effect on employee performance with a p-value of 0.270 > 0.05. These findings indicate that improving work professionalism and work engagement can significantly enhance employee performance.